Echinochrome pigment attenuates diabetic nephropathy in the models of type 1 and type 2 diabetes - Amel Mahmoud Soliman; Ayman Saber Mohamed; Mohamed-Assem Said Marie (Сахарный диабет)
Background. The main complication of diabetes mellitus is diabetic nephropathy in both types, which is a main reason for renal failure. Echinochrome substance present in sea urchin shells and spines and possesses high antioxidant activity.Aim. is to evaluate the ability of Ech to suppress the progression of diabetic complication in kidney.Materials and methods. Thirty-six male Wistar albino rats were divided into two main groups, type 1 diabetes mellitus and type 2 diabetes mellitus. Both groups divided into control, diabetic and echinochrome subgroups. Type 1 diabetes was induced by single dose of streptozotocin (60 mg/kg, i.p), while type 2 was induced by high fat diet for 4 weeks before the injection with streptozotocin (30 mg/kg, i.p). The treated groups were administrated by echinochrome (1mg/kg body weight in 10% DMSO) daily for 4 weeks.Results. Echinochrome groups showed reduction in the concentrations of glucose, malondialdehyde, urea, uric acid and creatinine. While it caused general increase in glutathione-S-transferase, superoxide dismutase, catalase, glutathione reduced, nitric oxide and creatinine clearance. The histopathological investigation showed clear improvement in the kidney architecture.Conclusion. Administration of echinochrome improves renal function and ameliorates renal histopathological changes possibly by improvement of glucose metabolism and inhibition of lipid peroxidation process.